Nursing Diagnoses in Acute Stroke Patients at the Emergency Department: Original Article - Hidayati, Nur; Aldianti, Elfa; Hanafi, Aprelia Afidatul; Phutthikhamin, Nichapatr (Babali Nursing Research, 2024)
Introduction: Stroke is the second leading cause of death and the third leading cause of disability worldwide. Nurses play a crucial role in providing care for stroke patients. Accurate and precise nursing diagnoses serves as the foundation for providing appropriate nursing care. This study aims to identify nursing diagnoses in acute stroke patients based on the Indonesian Nursing Diagnosis Standards. Method. This study utilized a descriptive research design. The research sample consisted of 471 patients (205 hemorrhagic strokes; 266 ischemic strokes) selected through random sampling techniques. The data were collected from the medical records of stroke patients treated at the Emergency Department of Muhammadiyah Lamongan Hospital from January to December 2023. The research instrument employed was a summary sheet, and data were analyzed descriptively. Result. The results of this study indicate that common signs and symptoms in hemorrhagic stroke patients included headache, decreased level of consciousness, and increased blood pressure with widened pulse pressure. The most frequent nursing diagnoses observed were decreased intracranial adaptive capacity (87.3%), impaired physical mobility (70.7%), and verbal communication impairment (74.1%). Similarly, common signs and symptoms in ischemic stroke patients include difficulty moving extremities, decreased range of motion (ROM), and decreased muscle strength. The most frequent nursing diagnoses observed were impaired physical mobility (81.5%), risk for falls (57.5%), and decreased intracranial adaptive capacity (49.6%). Conclusion: There are differences in signs and symptoms between hemorrhagic stroke and ischemic stroke during the acute phase, as well as differences in primary nursing diagnoses. However, these distinctions may vary in subsequent phases depending on the severity of the disease and underlying comorbidities. Future researchers are encouraged to conduct real-time studies to promptly identify any missing data.